2022
DOI: 10.3390/foods11182815
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Grade and the Characteristic Flavor of PCT (Panyong Congou Black Tea)

Abstract: Panyong Congou black tea (PCT) is one of the most representative and historically famous Congou black teas in China and has been gaining more and more attention for its beneficial health properties. Currently, four grades of PCT are available, based on the raw leaf materials and consumer palatability. The chemical profiles distinguishing different grades of PCT are yet to be defined, nor has the relationship with grade been evaluated. In the present study, chemometric analysis showed that epigallocatechin (EGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…After filtration, the tea residue was extracted again for 45 min using the same operation, and the two tea extracts obtained were mixed, concentrated, freeze-dried, and then stored at −80 °C for later experimental use. The AOT extracts were filtered through a 0.22 μm membrane and then subjected to biochemical methods ( Gao et al, 2022 ) and high-performance liquid chromatography (HPLC, Waters 2695, MA, USA) for the determination of the main active biochemical components. The conditions for a HPLC configured with a 2998 PDA detector are set as follows: mobile phase A: 2 % acetic acid, mobile phase B: acetonitrile, flow rate set to 1.0 mL/min; each injection volume was 10ul, wavelength: 280 nm, column temperature 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…After filtration, the tea residue was extracted again for 45 min using the same operation, and the two tea extracts obtained were mixed, concentrated, freeze-dried, and then stored at −80 °C for later experimental use. The AOT extracts were filtered through a 0.22 μm membrane and then subjected to biochemical methods ( Gao et al, 2022 ) and high-performance liquid chromatography (HPLC, Waters 2695, MA, USA) for the determination of the main active biochemical components. The conditions for a HPLC configured with a 2998 PDA detector are set as follows: mobile phase A: 2 % acetic acid, mobile phase B: acetonitrile, flow rate set to 1.0 mL/min; each injection volume was 10ul, wavelength: 280 nm, column temperature 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Six of the measured compounds, ECG, EGC, EGCG, GC, GCG, and theanine, differed significantly in all teas (Figure 2A), which suggested that they may have been the main non-volatile components shaping the taste differences among the three HSGTs. A multivariate statistical analysis, OPLS-DA, which amplifies between-group differences and minimizes within-group differences, was used to visually simplify the HPLC results [35][36][37]. The score plot (Figure 2B) shows that the three HSGTs were clearly distinct in terms of their non-volatile profiles.…”
Section: Quantification Of Caffeine Catechins and Theanine In Hsgtsmentioning
confidence: 99%
“…Black tea, as a recognized healthy beverage, has a long consumption history in the world, and it accounts for nearly 78% of the global tea consumption [ 1 ]. According to the processing technology used, black tea can be divided into three types, i.e., broken black tea, Congou black tea, and Souchoug black tea [ 2 ]. Among these, Congou black tea is popularly favored by consumers due to its elegant appearance, mellow taste, and sweet aroma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%